Shoaling of abyssal ventilation in the Eastern Indian Sector of the Southern Ocean - Shimada, Keishi; Kitade, Yujiro; 北出, 裕二郎; キタデ, ユウジロウ; Aoki, Shigeru; Mizobata, Kohei; 溝端, 浩平; ミゾバタ, コウヘイ; Cheng, Lingqiao; Takahashi, Kunio; Makabe, Ryosuke; 真壁, 竜介; et al. (Communications Earth & Environment, 2022)
Antarctic Bottom Water formation, which ventilates the abyssal layers of the Southern Ocean, is an integral component of the global ocean meridional overturning circulation. Considering evident freshening and density decreases in the source waters, widespread warming in the Southern Ocean suggests a weakening in the Antarctic Bottom Water supply. We demonstrate that the weakening is robust based on water mass warming in the deep and abyssal layers of the Australian-Antarctic Basin, which remained after removing the southward shift effect of the Southern Antarctic Circumpolar Current Front. Moreover, a decrease in apparent oxygen utilisation and reduced warming in the intermediate density layer below Circumpolar Deep Water extended further from the Australian-Antarctic Basin to the South Australian Basin. We suggest that a concurrent weakening in the densest portion and strengthening in the less dense portion shape the multi-basin change in the meridional overturning circulation that originates from the Southern Ocean. この論文のプレスリリースはこちら : http://id.nii.ac.jp/1342/00002394/ 15H01726 21H03587 journal article